2018
DOI: 10.1016/j.jdsr.2017.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Molecularly-targeted therapy for the oral cancer stem cells

Abstract: SummaryHuman cancer tissues are heterogeneous in nature and become differentiated during expansion of cancer stem cells (CSCs). CSCs initiate tumorigenesis, and are involved in tumor recurrence and metastasis. Furthermore, data show that CSCs are highly resistant to anticancer drugs. Cetuximab, a specific anti-epidermal growth factor receptor (EGFR) monoclonal antibody, is used in cancer treatment. Although development of resistance to cetuximab is well recognized, the underlying mechanisms remain unclear. Lap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 58 publications
1
16
0
Order By: Relevance
“…In this study, we utilized live-cell imaging and time-lapse analysis, which revealed that cetuximab treatment significantly reduced cell motility. Previous investigators reached the same conclusion after performing cell-migration assays 25 , 42 , 43 . Thus, we conclude that reduced cell motility was associated with a high cell density.…”
Section: Discussionsupporting
confidence: 53%
“…In this study, we utilized live-cell imaging and time-lapse analysis, which revealed that cetuximab treatment significantly reduced cell motility. Previous investigators reached the same conclusion after performing cell-migration assays 25 , 42 , 43 . Thus, we conclude that reduced cell motility was associated with a high cell density.…”
Section: Discussionsupporting
confidence: 53%
“… 2 In recent years, with the development of targeted drugs, the prognosis for patients with OSCC has been extended. 14 , 15 Immune checkpoint inhibitors have also shed light on the treatment of OSCC, and inflammation and immunity have been involved in the development of OSCC. 16 However, the immunological characteristics of OSCC are still largely uncovered.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies on the pathogenesis of oral cancer have identified a considerable number of molecular pathways involved in the development and progression of this disease ( 8 , 9 ). In effect, some of the altered signaling pathways involved in oral cancer have been proven to be potential targets for the development of anti-cancer therapies ( 10 ). Long non-coding RNAs (lncRNAs, >200 nt) encode no proteins but participate in cancer biology by regulating cancer-related gene expression ( 11 , 12 ).…”
Section: Introductionmentioning
confidence: 99%